Mineral balance in infantile cortical hyperostosis: effects of corticosteroids. Issue 1 (January 1991) - Barr, D G; Belton, N R
Abstract : The effects on mineral metabolism of therapeutic doses of corticosteroids were investigated in infantile cortical hyperostosis; in four untreated cases the calcium, phosphorus, and magnesium balances were strongly positive. In one severe case, treatment with prednisolone was associated with an alteration to negative calcium and magnesium balance, and faecal losses of calcium were particularly high. This effect persisted for at least three months after the steroids had been discontinued, and during this period there was pronounced retardation of linear growth. Six months after the treatment had been stopped mineral balance was again positive and there was rapid 'catch up' in growth. In infancy, the negative effect of corticosteroids on calcium, phosphorus, and magnesium metabolism may contribute to inhibition of bone growth and steroid stunting.